Que lindo o que vocês fizeram! - Brazilian Portuguese wh-exclamatives and the evidence for a split force - Medeiros Junior, Paulo; Sieiro, Pedro Luiz Moraes (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2021)
Portuguese exhibits a great variety of wh-exclamative sentences, including sentential exclamatives, which are the main concern of this paper. Brazilian Portuguese sentential wh-exclamatives seem to provide evidence to propose a split Force in the periphery of the sentence (RIZZI, 1997) when one considers the cooccurrence of a relative and an exclamative in the same utterance. We assume there are at least two functional heads available in Force: a RelP (hosting relative WHs) and an ExclP, supposed to host exclamative WHs; analyzed data also show that exclamation must be higher than relativization in a Split Force projection, with some more place above ExclP for topicalizing other syntactic objects.